The Value Of Indonesian Unity Learning In The Historical Education Study Progtam Of Galuh University - Terra Erlina (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
This study aims to determine the inculcation of nationalism values and the difficulties experienced by lecturers, and to find out the values contained in point three of Pancasila. This study uses a qualitative method. Data were collected through observation, in-depth interviews, and documentation. The results showed the process of planting the values of nationalism and the difficulties faced by the lecturers History in the process of instilling the values of nationalism is due to the backgrounds of students with different characters and a lack of understanding of the meaning of nationalism itself. As well as the values contained in the third principle of the Indonesian Unity, namely The values of nationalism, love of the country, willing to sacrifice, cutting and steadfast, responsible and trustworthy.